2016
DOI: 10.1136/bmjopen-2016-011642
|View full text |Cite
|
Sign up to set email alerts
|

Is it worth screening elective orthopaedic patients for carriage ofStaphylococcus aureus? A part-retrospective case–control study in a Scottish hospital

Abstract: BackgroundWith recent focus on methicillin-resistant Staphylococcus aureus (MRSA) screening, methicillin-susceptible S. aureus (MSSA) has been overlooked. MSSA infections are costly and debilitating in orthopaedic surgery.MethodsWe broadened MRSA screening to include MSSA for elective orthopaedic patients. Preoperative decolonisation was offered if appropriate. Elective and trauma patients were audited for staphylococcal infection during 2 6-month periods (A: January to June 2013 MRSA screening; B: January to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“… 30 S. aureus screening and eradication programmes prior to elective orthopaedic surgery have a reported relative risk reduction of 66.4% (95% CI 45.8 to 87.0) for the prevention of S. aureus SSI. 18 , 30 - 34 According to economic estimates in the United States, the hospital treatment costs for an individual patient with prosthetic joint infection (PJI) range from $30 000 to $120 000. 35 - 37 Estimates in the United Kingdom for total hospital care costs per case are similar to that in the United States (between £20 000 and £100 000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 S. aureus screening and eradication programmes prior to elective orthopaedic surgery have a reported relative risk reduction of 66.4% (95% CI 45.8 to 87.0) for the prevention of S. aureus SSI. 18 , 30 - 34 According to economic estimates in the United States, the hospital treatment costs for an individual patient with prosthetic joint infection (PJI) range from $30 000 to $120 000. 35 - 37 Estimates in the United Kingdom for total hospital care costs per case are similar to that in the United States (between £20 000 and £100 000).…”
Section: Resultsmentioning
confidence: 99%
“… 17 A recent retrospective part cohort United Kingdom-based study among patients undergoing elective orthopaedic surgery reported a threefold reduction in MSSA -associated SSI, using a routine preoperative screening and decolonization programme. 18 In contrast to MSSA, MRSA prevalence in healthy community individuals is estimated to be < 2%. 19 Screening of patients presenting for surgery or admitted to hospital areas with strong risk factors for MRSA , such as intensive care units (ICUs), dialysis units, and elderly care areas, is widely practised in healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…Combined screening for MRSA and MSSA has thus been suggested because a reduced risk of infection caused by S. aureus might outweigh the extra costs of additional screening [30]. Several studies provided evidence for the value of pre-operative screening for S. aureus and subsequent decolonisation in the reduction of hospital-acquired SSIs caused by this pathogen [24,31].…”
Section: Staphylococcus Aureus Colonisationmentioning
confidence: 99%
“…aureus decolonization is daily body washes with an antiseptic for five days plus an intranasal antibiotic ointment, given three times a day. For MRSA positive patients, 2% mupirocin is often applied intranasally; for MSSA positive patients, Naseptin Nasal Cream (chlorhexidine hydrochloride 0.1%; neomycin sulfate 0.5%) can be used [ 27 ]. Eradication of the MRSA carrier state was achieved in up to 88% of healthcare workers [ 20 ].…”
Section: Commentarymentioning
confidence: 99%